How to Assess and Prevent Risk of Diabetic Foot Ulcer - Kharisma Pratama; Wuriani Wuriani; Cau Kim Jiu; Syahid Amrullah; Jaka Pradika; Yenni Lukita; Usman Usman; Hartono Hartono; Indri Erwhani (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The discovery of problems related to health status was the beginning of the idea to carry out activities with the basic theme